Epigenomics and Early Life Human Humoral Immunity: Novel Paradigms and Research Opportunities - Gutierrez, Maria J.; Nino, Gustavo; Hong, Xiumei; Wang, Xiaobin (Frontiers in Immunology, 2020)
The molecular machinery controlling immune development has been extensively investigated. Studies in animal models and adult individuals have revealed fundamental mechanisms of disease and have been essential to understanding how humans sense and respond to cellular stress, tissue damage, pathogens and their environment. Nonetheless, our understanding of how immune responses originate during human development is just starting to emerge. In particular, studies to unveil how environmental and other non-heritable factors shape the immune system at the beginning of life offer great promise to yield important knowledge about determinants of normal inter-individual immune variation and to prevent and treat many human diseases. In this review, we summarize our current understanding of some of the mechanisms determining early life antibody production as a model of an immune process with sequential molecular checkpoints susceptible to influence by non-heritable factors. We discuss the potential of epigenomics as a valuable approach that may reveal not only relevant gene-environment interactions but important clues about immune developmental processes and homeostasis in early life. We then highlight the novel paradigm of human immunology as a complex field that nowadays requires a longitudinal systems-biology approach to understand normal variation and developmental changes during the first few years of life.